Broadband EM Performance Characteristics of Single Square Loop FSS Embedded Monolithic Radome - Raveendranath U. Nair; J. Madhumitha; Rakesh M. Jha (International Journal of Antennas and Propagation)
A monolithic half-wave radome panel, centrally loaded with aperture-type single square loop frequency selective surface (SSL-FSS), is proposed here for broadband airborne radome applications. Equivalent transmission line method in conjunction with equivalent circuit model (ECM) is used for modeling the SSL-FSS embedded monolithic half-wave radome panel and evaluating radome performance parameters. The design parameters of the SSL-FSS are optimized at different angles of incidence such that the new radome wall configuration offers superior EM performance from L-band to X-band as compared to the conventional monolithic half-wave slab of identical material and thickness. The superior EM performance of SSL-FSS embedded monolithic radome wall makes it suitable for the design of normal incidence and streamlined airborne radomes.